2009
DOI: 10.4103/0250-474x.58190
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous estimation of amlodipine besilate and olmesartan medoxomil in pharmaceutical dosage form

Abstract: Two UV Spectrophotometric and one reverse phase high performance liquid chromatography methods have been developed for the simultaneous estimation of amlodipine besilate and olmesartan medoxomil in tablet dosage form. First UV spectrophotometric method was a determination using the simultaneous equation method at 237.5 nm and 255.5 nm over the concentration range 10-50 μg/ml and 10-50 μg/ml, for amlodipine besilate and olmesartan medoxomil with accuracy 100.09%, and 100.22% respectively. Second UV spectrophoto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…The absorbance of various dilutions of CIL and OLME in diluents was measured at λ 2 and λ 3 . At these two wavelength absorbance difference of CIL at any concentration level was found to be zero while for OLME, absorbance difference was found to increase concomitantly as concentration was increase [6][7][8][9][10][11].…”
Section: Selection Of Wavelength For Estimation Of Cil and Olmementioning
confidence: 99%
“…The absorbance of various dilutions of CIL and OLME in diluents was measured at λ 2 and λ 3 . At these two wavelength absorbance difference of CIL at any concentration level was found to be zero while for OLME, absorbance difference was found to increase concomitantly as concentration was increase [6][7][8][9][10][11].…”
Section: Selection Of Wavelength For Estimation Of Cil and Olmementioning
confidence: 99%
“…Amlodipine besylate is official in IP [2] and BP [3] and Hydrochlorthiazide is official in IP [2], BP [3] and USP [4]. Literature survey revealed that various methods such as UV [9,10,15,16,19,20], HPLC [11,17], HPTLC [12,18], LC-MS/MS [13] and UPLC [14] are available in single and combination with other drugs. However, no spectrophotometric method has yet been reported for simultaneous estimation of amlodipine besylate, olmesartan medoxomil and hydrochlorthiazide in tablet dosage forms.…”
Section: Amlodipine Besylate (Figure 1a) [1] Is 3-ethyl 5-methyl (4rsmentioning
confidence: 99%
“…The literature survey reveals that, few analytical methods are available for the assay of ADB /OSM in tablets by spectrophotometric techniques [8][9][10], few articles by the HPLC methods for ADB /OSM tablets [11][12][13] and one method which describe the estimation of impurities alone which was published on combination product by using UPLC technique [14]. However, UPLC technique is very costly and complex instrument having very tedious procedure.…”
Section: Introductionmentioning
confidence: 99%